The Dispute Settlements of Inheritance in Palangka Raya: A Legal Anthropology Approach (UINSI Samarinda, 2019)
The issue of inheritance distribution does not often lead to conflicts that must be resolved by means of litigation. In resolving conflicts that might arise, the community usually has set a separate rule to distribute inheritance. The people of Central Kalimantan, especially in the City of Palangka Raya, prioritize deliberations that are actually not contrary to Islamic law in resolving their inheritance disputes. Why and how these dispute settlements are conducted? This study uses normative-empirical methods which employs a legal anthropology approach. The results of the study show that the tradition of resolving inheritance disputes in the people of Palangka Raya City of Central Kalimantan prioritizes peaceful settlement disputes by using Islamic law first and then a family meeting is held to determine the agreeable share and distribution of assets. The principle of kinship in the protection of property (hifz al-maal) in the family is adopted, so that the community returns to share property with the negotiation method which is built on family agreements. By referring to Islamic jurisprudence on inheritance, the dispute settlements also aims at sharia compliant in order to adhere to Islamic doctrine (hifz al-din). Finally, they also adopt the principle of responsive thinking which is human based on local wisdom values in society. The conclusion of this study shows that the Palangka Raya City Society combines Islamic law and customary law in the distribution of inheritance.Keywords: dispute resolution, inheritance, Palangka Raya, legal anthropology.